Tcheffa valley study. Contributory paper no. 1: Land use, vegetation and agro-ecological description - International Livestock Centre for Africa (International Livestock Centre for Africa, 1983)
Describes the location, soil & rainfall patterns in the Tcheffa valley, dividing the area into four agro-ecological units & examining the land use pattern, the natural vegetation from 1957 to 1982, introduced vegetation, agricultural practices, grazing periods & livestock utilization levels.